A review on media clogging in attached growth system - Hayder G.; Ahmed A.N.; Fuad N.F.S.M. (Research India Publications, 2023)
Attached growth system is widely used nowadays as a biological wastewater treatment which used a support medium as a physical bed for biomass growth such as wood, gravel, sand, rock and wide range of synthetic plastic material. However, limitation in attached growth system is rarely been discussed in details. Based from the review, it shows that the major drawback of attached growth system is media clogging. Bio film thickness, slow water flow, selection of media (media type, media size and surface area, and media void), lack of aeration, lack of backwashing and mechanical failure has been reported caused media clogging. This paper presents a review of one of the problems encountered with attached growth system which is media clogging in approaches to enhance the performance of the biological process in wastewater treatment. Research India Publications.